Violent Behavior and Learners’ Performance Difficulties - Patrice-Aimé, Djelle Opely; Haoua, Coulibaly (European Scientific Journal, ESJ, 2020)
This study aims to know the effects of psycho-emotional problems caused by school violence, both to students and teachers. Hence, the hypothesis is that violence has an impact on students’ and teachers’ performance. As for our sample, it comprises 250 students, divided into three groups. Concerning our analysis methods, we chose the Multiple Correspondence Factor Analysis (MCA) as a multidimensional analysis method and the Hierarchical Ascending Classification (HAC) for the classification. Finally, our data analysis reveals a link between attachment schemes and learning difficulties. This link is different depending on whether the attachment schemes are related to family or teachers.